PERTANGGUNG JAWABAN SUPERMARKET DALAM PENITIPAN BARANG DI KOTA SAMARINDA MENURUT UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Joldi Sandi Wijaya (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractSupermarkets offer excessive safety and convenience for consumers who shop where consumers have rights to comfort, security, and safety in consuming goods and services. Has the formulation and limitation of the issue of how the supermarket is responsible for damage or loss and procedures for filing lost claims. The research carried out aims to determine the security system and responsibilities of supermarkets related to the safekeeping of goods in accordance with the Civil Code and the Consumer Protection Act. This research uses normative legal research that is a legal research method that is carried out by examining library materials or secondary data only with the Law Approach (Statue Approach) and Conceptual Approach (Conceptual Approach). Research shows that the responsibility of supermarkets in Samarinda in terms of Safekeeping of Goods is in accordance with applicable legal provisions starting with the obligation to maintain goods that are deposited and return goods that have been deposited in an "in-kind" condition or more precisely in circumstances beginning. The responsibility of the supermarket to the injured consumer is to provide compensation in the form of cash or the replacement of goods of the same value and equivalent and the compensation has been determined by the supermarket. The Customer brings evidence of loss reports to the Supermarket deposit holder. The form of settlement carried out by the Supermarket deposit holder can be in the form of goods or money in accordance with the agreement that has been negotiated.